Transformational Security Awareness: What Neuroscientists, Storytellers, and Marketers Can Teach Us About Driving Secure Behaviors - Carpenter (Wiley Data and Cybersecurity, 2019)
Monograph
fulltext
Keywords: Communication, Networking and Broadcast Technologies